Common psychiatric symptoms among public school teachers in Palmas, Tocantins, Brazil: An observational cross-sectional study - Baldaçara, Leonardo; Silva, Álvaro Ferreira; Castro, José Gerley Díaz; Carvalho, Gessi de (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Teachers are at great risk of physical and mental stress due to material or psychological difficulties associated with their work. This study aimed to assess the prevalence of common psychiatric symptoms measured on the Self-Reporting Questionnaire (SRQ-20) scale that would suggest a diagnosis of psychiatric disorders among public school teachers in Palmas, Tocantins, Brazil, in 2012. DESIGN AND SETTING: Observational cross-sectional study in Palmas, Tocantins, Brazil. METHOD: We assessed 110 municipal teachers in the city of Palmas, Tocantins, Brazil. They were selected randomly from a list of employees of the Municipal Education Department of Palmas. All of them answered the SRQ-20 questionnaire after giving their consent. RESULTS: Between the years 2008 and 2011, 24 cases of absence from work due to mental disorders were found. We excluded one case and 109 teachers answered the SRQ-20questionnaire. Out of the 109 teachers assessed, 54 had ≥ 7 points on the SRQ-20 scale. This finding suggests that 49.5% of the teachers had symptoms that were sufficient to consider a diagnosis of mental disorder, with the need for treatment. CONCLUSION: Our study found that the prevalence of mental disorders among teachers is as high as seen in the literature. Our results suggest that recognition of mental disorders is low and that the current statistics fail to reach the occupational health sector.